Respuesta :

This seems like a lot more work than it is, but here we go
Simplifying8 + -2y = 3y + -2
 Reorder the terms: 8 + -2y = -2 + 3y
 Solving 8 + -2y = -2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right.
  Add '-3y' to each side of the equation. 8 + -2y + -3y = -2 + 3y + -3y Combine like terms: -2y + -3y = -5y 8 + -5y = -2 + 3y + -3y
 Combine like terms: 3y + -3y = 0 8 + -5y = -2 + 0 8 + -5y = -2 Add '-8' to each side of the equation. 8 + -8 + -5y = -2 + -8
 Combine like terms: 8 + -8 = 0 0 + -5y = -2 + -8 -5y = -2 + -8 Combine like terms: -2 + -8 = -10 -5y = -10
  Divide each side by '-5'. y = 2
 Simplifying y = 2
Y equals 2. is that your question